Giant magnetoimpedance and magneto-optical Kerr effects in (Co63Ni37)75Si15B10 amorphous ribbon. (October 2020) - Corte-Leon, P.; Zhukova, V.; Dominquez, L.; Blanco, J.M.; Ipatov, M.; Chizhik, A.; Zhukov, A.; Gonzalez, J.
Abstract: The Giant magneto-impedance (GMI) effect in the frequency range 10–1000 MHz and surface magnetic characterization using the magneto-optical Kerr effect (MOKE) in (Co63 Ni37 )75 Si15 B10 amorphous ribbon were studied. The GMI ratio increases with a frequency up to around 500 MHz followed by a slow decrease. Observed dependence of GMI ratio is discussed by considering the frequency dependencies of the skin depth penetration and magnetic permeability. MOKE in the transverse and longitudinal applied magnetic field to the ribbon direction configurations provides images of magnetic domain structure and hysteresis loops of the two surface sides of the ribbon. An inclined magnetic structure with respect to the longitudinal direction of the ribbon was observed. This inclined magnetic structure is related to a significant transverse component of the magnetic susceptibility tensor, which is a prerequisite to observe GMI effect. The magnetic anisotropy field evaluated from the hysteresis loop with the transverse applied magnetic field configuration is in agreement with the longitudinal magnetic field necessary to obtain the maximum GMI ratio. The MOKE characteristic of two sides ribbon is quite vertical associated to large Barkhausen jumps because the anisotropy axis is, in this configuration, parallel to the applied magnetic field. Highlights: The GMI ratio increases with a frequency up to around 500 MHz followed by a slow decrease. Inclined magnetic structure is related to a significant transverse component of the magnetic susceptibility tensor. MOKE characteristic of two sides ribbon is associated to large Barkhausen jumps.